Sosialisasi Anti Bulying Sebagai Sarana Mempersiapkan Generasi Emas Sdn 1 Kumpulrejo - M. Syihabuddin Ibnu Achmad; Diana Nur Fatimah; Endiana Silviani; Mohamad Khafid Maulana; Mustafa Solehudin; Agustina Intan Salsabila; Muhammad Khudori (Jurnal Kemitraan Masyarakat, 2024)
To achieve progress and development based on the standards that are used as references, the education process is carried out. Education can help people grow into people with character and are productive every day. But in the world of education, a problem arises such as bullying that can threaten students in education. This study aims to reveal the negative impacts of bullying and find a way out of the problem in order to prepare the golden Indonesian nation. The method of implementing anti-bullying socialization is carried out in three stages: planning, implementation, and evaluation. At the planning stage, several things have been determined, including the location and date of the activity, namely at SDN 1 Kumpulrejo, Kumpulrejo Village, Patebon District, Kendal Regency. In addition, a one-day schedule has been made for socialization, material on physical violence to the presentation of material on the language of the impact of bullying. At the implementation stage, socialization is carried out by showing anti-bullying animation videos, presenting material on bullying behavior, verbal violence, and physical. The results of this study indicate that bullying is an act of intimidating and forcing a weaker person or group to do something against their will with the intention of causing physical or mental harm through delivery and attack. Bullying itself has a negative impact on students because it can make victims lose their confidence and feel traumatized. So that with the existence of anti-bullying socialization, bullying behavior in the world of education can be overcome.